The Importance of Learning Style in End-User Training1 - Bostrom, Robert P.; Olfman, Lome; Sein, Maung K. (MIS Quarterly, 1990)
The importance of effective training in ensuring the success of end-user computing (EUC) has been emphasized by several researchers in information systems. A vast amount of evidence from research in related areas such as educational psychology suggests that individual differences, such as learning style, may affect users learning about a new EUC software package. This article reports the findings of a series of studies that examine the influence of a novice’s learning style in learning typical EUC tools such as spreadsheets and electronic mail. A consistent pattern of findings emerges that indicates that learning modes is an important predictor of learning performance, both by itself and in interaction with training methods. The findings suggest that in the design of training, it is essential to match training methods to individual difference variables. Based on these findings, guidelines are recommended for IS professionals involved in EUC training and further research directions are discussed.